MOOC Makers: Professors’ Experiences With Developing and Delivering MOOCs - Blackmon, Stephanie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Massive open online courses (MOOCs) have been described as purposeful educational resources for teaching, open educational initiatives, competency-based learning, and the like. They have also been described as an agent of higher education’s deterioration. Although MOOCs are often discussed in terms of their current and future usefulness, or lack thereof, in higher education contexts, very little data exists on professors’ experiences creating and teaching these courses. Therefore, I conducted a qualitative study, more specifically a phenomenography, to examine professors’ experiences with developing and teaching a MOOC. Data include their thoughts on why they decided to teach a MOOC and the benefits and challenges associated with making and teaching a MOOC.